The Effectiveness of Flipbook and Video to Improve Students' Critical Thinking Skills in Science Learning during the COVID-19 Pandemic - Ulin Nuha; Sri Wahyuni; Aris Singgih Budiarso; Uswatun Hasanah; Novita Eka Anggraini (Lensa: Jurnal Kependidikan Fisika, 2021)
Critical thinking is one of the skills that must be possessed in studying science. During the Covid-19 pandemic, flipbooks and videos can be used as alternative media to improve students' critical thinking skills. This study aims to determine the effectiveness of using flipbooks and videos in improving the critical thinking skills of junior high school students during the pandemic. The method used in this research is descriptive quantitative. The data collected were in the form of students' pretest and posttest scores. The data were analyzed using the N-gain test and Independent Sample T-Test. The results showed: (1) learning videos were effective for improving students' critical thinking skills with an average score of 0.44 (medium) and (2) flipbooks were effective for improving students' critical thinking skills with an average score of 0.42 (medium). There is no significant difference between students' critical thinking skills, both after using flipbooks and videos.